Reforma a vapor do ácido acético sobre catalisadores de Ni/Al2O3: estudo das rotas reacionais - Burak, Jorge Augusto Mendes (2014)
Acetic acid (AA), one majority substance contained in the bio-oil from biomass pyrolysis, was used as a model molecule for study of reaction routes of steam reforming on Ni/θ-Al2O3 catalysts. The catalyst containing 15% nickel (w/w), prepared by wet impregnation in a θ-Al2O3. The samples were characterized: nitrogen adsorption, ammonia desorption, X-ray diffraction, temperature programmed reduction and thermogravimetric analysis. The reaction routes were studied using: a) temperature programmed desorption (TPD), b) temperature programmed decomposition e c) temperature programmed steam reforming (TPSR) with ratios of 3:1, 6:1 or 9:1 of H2O: AA. The results of TPD where AA was adsorbed and decomposed in function of temperature, show simultaneous desorption of CO, CO2, H2 and CH4 which is explained by the formation of acetic anhydride on the surface of Ni which decomposes into CH3COO* and/or CH3CO* and then CO, CO2 and H2. The TPSR results suggest that the reaction route of decomposition and reform of AA depend on the temperature and the ratio H2O:AA. At low temperatures (< 650 K) and low ratios H2O:AA has the formation of CO and CO2 via bond breaking C-C of species CH3COO* and CH3CO* formed from acetic anhydride. With increasing temperature the anhydride formation is disfavored, in region between 600-800 K, there is interaction and dimerization of AA molecule adsorbed on Ni, which leads to the formation of C2H4. At the same time to this reaction, the formation of CH4 is verified by the hydrogenation CH3* species formed by breaking of CH3COO* and/or CH3CO* species. In high temperatures (> 800 K) methane formation is favored, possibly by decomposition of species CH3 in C* e H2, C* is oxidized by water. In highest ratio (9:1), the formation of the anhydride is not favored and the reforming reactions occur via decomposition of CH3COO* species. In low temperature, formation of CH4 is not observed and the oxidation of CH3* species may occur via the formation of formates. With increasing temperature oxidation of these CH3* radicals via pyrolytic should be favored.